PENGARUH PRIVASI, KEAMANAN, KEPERCAYAAN, DAN PENGALAMAN TERHADAP NIAT UNTUK BERTRANSAKSI SECARA ONLINE - Farina, Khoirina (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2016)
The objective of this study is to examine the influence of privacy, security, trust, and experience on the intention to transact online. Data were obtained from questionnaires that contains a list of questions given to 65 students of S2 in Jakarta. This study uses Structural Equation Model (SEM). The results of this study that (1) Indicators of security, trust and privacy have negative significant influence to perceptions of risk, (2) trust and perceptions of risk have positive significant influence to attitudes, (3) attitudes, risk perception and experience of using internet have positive significant influence to the intention to transaction online. (4) subjective norms have negative and no significant. (5) controls the behavior of the negative and no significant influence on the intention. The result is expected to increase the knowledge and are expected to contribute in the development of e-business systems